Exposure to methylene chloride. Content in subcutaneous adipose tissue. - Engström, Jörgen; Bjurström, Rasmus (Scandinavian Journal of Work, Environment & Health, 1977)
The fat content of the body was calculated in 12 healthy male subjects aged 21 to 35 years by means of hydrostatic weighing and anthropometric estimation of skeletal weight. The subjects were exposed to a concentration of 2,600 mg of methylene chloride per cubic meter of inspired air (750 ppm) for 1 h while performing work at an intensity of 50 W on a bicycle ergometer. The uptake in the organism was measured continuously with the Douglas bag technique. The amount of methylene chloride absorbed correlated highly with degree of obesity and body weight. Needle biopsy specimens of subcutaneous adipose tissue were taken from the buttocks before exposure and 0, 1, 2, 3 and 4 h after exposure. The mean yield of tissue from the 72 biopsies was 25 mg. The concentration of methylene chloride in the adipose tissue was determined by gas chromatography, using a headspace method. The mean concentration was 10.2 mg/kg 1 h after exposure and 8.4 mg/kg after 4 h. There was a wide distribution around the mean values. In the six slim subjects the concentration in the adipose tissue during the 4 h after exposure was on an average twice that of the six more obese subjects. On the other hand, in spite of lower concentrations, the obese subjects had a greater calculated amount of methylene chloride in the total fat depots of the body. Two subjects were studied about 22 h after exposure, the concentration in subcutaneous adipose tissue being 1.6 and 1.7 mg/kg, respectively, at that time.
Keywords: adipose tissue; alveolar air concentration; body fat concentration; exercise; exposure; man; methylene chloride; subcutaneous adipose tissue